Keabsahan Jual Beli Atas Rumah Dengan Perjanjian Di Bawah Tangan yang Hendak Di Buatkan Akta Jual Beli Tanpa Adanya Pihak Penjual - monica lidiyana; Mella Ismelina Farma Rahayu (Magister Kenotariatan, Universitas Jambi, 2021)
The sale and purchase of house rights is based on the provisions of Article 37 Paragraph 1 of Government Regulation Number 24 of 1997, which in essence, the transfer of land rights must be proven by a deed made by Land Titles Registrar, but some people who are still lay people often think that the sale and purchase of land It is enough to do it by using receipts in full, so that when you want to reverse the name register, of course the effort is hampered, because there is no the sale and purchase of land deed made by Land Titles Registrar, the obstacles also increase, when one of the parties, especially the seller, is unknown, so that the sale and purchase of land deed cannot be made, because making the sale and purchase of land deed must involve the seller and the buyer. This research was conducted using the Normative Juridical Law Research method, this research was conducted using secondary data, which is divided into primary, secondary and tertiary legal materials. What will be examined in this research is related to the validity of the sale and purchase of land which is only proven by the receipt, the validity of the sale and purchase deed of land made by Land Titles Registrar without the seller, and the implementation of the sale and purchase deed by the Land Deed Making Official on land without a seller in Decision Number 256 / PDT. G / 2019 / PN Ckr.